Purification of Dengue Virus Particles by One-Step Ceramic Hydroxyapatite Chromatography - Kurosawa, Yae; Saito, Maiko; Kobayashi, Shintaro; Okuyama, Tsuneo (Scientific Research, 2012)
Dengue virus type 2 ThNH7/93 retained infectious activity after purification by ceramic hydroxyapatite chromatography. Dengue virus type 2 culture fluid was loaded onto the ceramic hydroxyapatite column and eluted with a linear gradient of sodium phosphate buffer. Culture fluid and protein contaminants derived from host cells were eluted initially, followed by elutions of dsDNA, and then dengue virus type 2. The recoveries of dengue virus type 2 were 64 ± 14% (n = 11) in the hemagglutination (HA) test and 60% (n = 2) determined by focus assay for viral infectivity. This protocol was highly reproducible, simple, rapid, and appears applicable to other virus species such as influenza virus, Japanese encephalitis virus and adenovirus
Keywords: Ceramic Hydroxyapatite; Virus Purification; Dengue Virus; Virus Particle; Virion